Genericity of confined chemical garden patterns with regard to changes in the reactants. Issue 19 (21st May 2015) - Haudin, Florence; Brasiliense, V.; Cartwright, Julyan H. E.; Brau, Fabian; De Wit, A.
<x xml:space="preserve">Abstract</x> Typical patterns emerging during the growth of chemical gardens in a confined geometry when the concentration of the reactants are changed. These patterns are robust to changes in the reactant ions.